Racing dragons and remembering aliens: Benefits of playing number and working memory games on kindergartners' numerical knowledge. Issue 4 (21st October 2019) - Ramani, Geetha B.; Daubert, Emily N.; Lin, Grace C.; Kamarsu, Snigdha; Wodzinski, Alaina; Jaeggi, Susanne M.
Abstract: Sources that contribute to variation in mathematical achievement include both numerical knowledge and general underlying cognitive processing abilities. The current study tested the benefits of tablet‐based training games that targeted each of these areas for improving the mathematical knowledge of kindergarten‐age children. We hypothesized that playing a number‐based game targeting numerical magnitude knowledge would improve children's broader numerical skills. We also hypothesized that the benefits of playing a working memory (WM) game would transfer to children's numerical knowledge given its important underlying role in mathematics achievement. Kindergarteners from diverse backgrounds ( n  = 148; 52% girls; M age  = 71.87 months) were randomly assigned to either play a number‐based game, a WM game, or a control game on a tablet for 10 sessions. Structural equation modeling was used to model children's learning gains in mathematics and WM across time. Overall, our results suggest that playing the number game improved kindergarten children's numerical knowledge at the latent level, and these improvements remained stable as assessed 1 month later. However, children in the WM group did not improve their numerical knowledge compared to children in the control condition. Playing both the number game and WM game improved children's WM at the latent level. Importantly, the WM group continued to improve their WM for at least a month after playing the games. The results demonstrate that computerized games that target both domain‐specific and domain‐general skills can benefit a broad range of kindergarten‐aged children. Abstract : We tested the benefits of engaging in tablet‐based games that target either domain‐specific or domaingeneral skills in a diverse population of kindergarten‐aged children. Structural equation modeling was used to determine children's learning gains in mathematics and working memory across time. The results suggest that computerized games that target both domain‐specific and domain‐general skills can lead to broad and longitudinal benefits that go beyond the trained task.